2007
DOI: 10.1086/518451
|View full text |Cite
|
Sign up to set email alerts
|

Point: Vancomycin Is Not Obsolete for the Treatment of Infection Caused by Methicillin-Resistant Staphylococcus aureus

Abstract: Since the discovery, development, and US Food and Drug Administration approval of vancomycin in the 1950s, this agent has remained a mainstay for the treatment of infections caused by methicillin-resistant Staphylococcus aureus (MRSA). However, because of the development of new antistaphylococcal antibiotics and reports of vancomycin failures, the utility of vancomycin has recently been questioned. Although vancomycin did not undergo the strict US Food and Drug Administration approval process that is in place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(103 citation statements)
references
References 39 publications
1
99
1
2
Order By: Relevance
“…21 A Monte Carlo simulation utilizing these pharmacokinetic data demonstrated that the high dose regimen had a 20% higher probability of achieving the pharmacodynamic target for MRSA isolates with a vancomycin MIC of 1 µg/ml, while pharmacodynamic target attainment rates for higher or lower MIC values were not significantly affected by dosing strategy. 22 Optimizing vancomycin dosing is important as 70% of MRSA isolates in a recent study had a vancomycin MIC of 1 µg/ml. 23 These data are not specific to obese patients, but the pharmacodynamic principles should transcend BMI classes.…”
Section: Discussionmentioning
confidence: 99%
“…21 A Monte Carlo simulation utilizing these pharmacokinetic data demonstrated that the high dose regimen had a 20% higher probability of achieving the pharmacodynamic target for MRSA isolates with a vancomycin MIC of 1 µg/ml, while pharmacodynamic target attainment rates for higher or lower MIC values were not significantly affected by dosing strategy. 22 Optimizing vancomycin dosing is important as 70% of MRSA isolates in a recent study had a vancomycin MIC of 1 µg/ml. 23 These data are not specific to obese patients, but the pharmacodynamic principles should transcend BMI classes.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy still exists over the current, non-methoddependent breakpoint of 2 mg/L, appreciating that if this were to be lowered further the majority of isolates would be deemed resistant [7]. A growing body of data showing significant variability both in minimum inhibitory concentration (MIC) measurements and accuracy of MIC determination demonstrates the importance of the method of susceptibility testing [8,9].…”
Section: Use Of Vancomycinmentioning
confidence: 99%
“…Therapeutic alternatives exist, as S. aureus remains highly susceptible to vancomycin, teicoplanin, linezolid, and quinupristin/dalfopristin [23]. Mohr and Murray also asserted that vancomycin is as a safe drug and alternative agent for MRSA infections, as it has no drug-drug interactions, can be administered fairly infrequently through a peripheral vein, and is inexpensive [24]. Another study recommended that penicillin should be used for infrequent penicillinsusceptible isolates, that oxacillin and nafcillin are to be considered the major option for penicillin-resistant staphylococci, and that glycopeptides are the drugs of choice for infections caused by MRSA or MRSE.…”
Section: Discussionmentioning
confidence: 99%